Nutritional assessment and serum zinc and copper concentration among children with acute lymphocytic leukemia: a longitudinal study - Sgarbieri, Ursula Rohr; Fisberg, Mauro; Tone, Luís Gonzaga; Latorre, Maria do Rosário Dias (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: When undergoing chemotherapy and/or radiotherapy, children with acute lymphocytic leukemia may present important nutritional disorders because of the gastrointestinal toxicity of most chemotherapy agents or the effects of radiation on the orga- nism. These patients may also present changes in their serum concentrations of trace elements such as zinc and copper. The present study aimed to follow anthropometric parameters and serum levels of zinc and copper in a group of children under treatment for acute lymphocytic leukemia. DESIGN AND SETTING: Longitudinal study, at the Pediatric Section of Hospital das Clínicas, Ribeirão Preto, Brazil. METHODS: Forty-five children with acute lymphocytic leukemia were studied. Anthropometric parameters such as weight and height and the daily intakes and serum levels of copper and zinc were recorded at diagnosis and during the treatment. RESULTS: During the initial phase of the treatment, there was an increase in energy intake accom- panied by weight gain. However, during the later phases of treatment there was a reduction in energy intake with accompanying weight loss. Decreased growth rate during treatment was more pronounced in children with high-risk acute lymphocytic leukemia, probably due to radiation therapy. Serum zinc levels remained basically unaltered during the treatment, whereas copper levels decreased dramatically with the beginning of treatment. CONCLUSIONS: The treatment given to children with acute lymphocytic leukemia has an important effect on their linear growth rate and nutritional status, and also on their serum copper levels.